2000
DOI: 10.1152/ajpcell.2000.279.3.c724
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ca2+ sensitivity of skeletal and cardiac muscle ryanodine receptors in the presence of calmodulin

Abstract: Calmodulin (CaM) activates the skeletal muscle ryanodine receptor Ca(2+) release channel (RyR1) in the presence of nanomolar Ca(2+) concentrations. However, the role of CaM activation in the mechanisms that control Ca(2+) release from the sarcoplasmic reticulum (SR) in skeletal muscle and in the heart remains unclear. In media that contained 100 nM Ca(2+), the rate of (45)Ca(2+) release from porcine skeletal muscle SR vesicles was increased approximately threefold in the presence of CaM (1 microM). In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
131
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 37 publications
9
131
1
Order By: Relevance
“…Skeletal muscle SR membrane vesicles were isolated from pig longissimus dorsi muscle by differential ultracentrifugation of homogenized muscle (5,18). Samples enriched in RyR1 were obtained by sucrose gradient fractionation of CHAPS-solubilized SR (23).…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal muscle SR membrane vesicles were isolated from pig longissimus dorsi muscle by differential ultracentrifugation of homogenized muscle (5,18). Samples enriched in RyR1 were obtained by sucrose gradient fractionation of CHAPS-solubilized SR (23).…”
Section: Methodsmentioning
confidence: 99%
“…In summary, all IP 3 R subtypes are inhibited by Ca 2þ -CaM, but the molecular basis of this inhibition has not been established. It seems, on balance, that CaM is unlikely to be the accessory protein through which Ca 2þ universally inhibits IP 3 R. That need not preclude a role for CaM in modulating IP 3 R function (Taylor and Laude 2002), just as it does for RyR (Chen et al 1997;Fruen et al 2000;Rodney et al 2001), but we must look elsewhere for the site through which Ca 2þ inhibits IP 3 R.…”
Section: Regulation Of Ip 3 Receptors By Ca 2þ and Ipmentioning
confidence: 99%
“…Direct CaM binding inhibits all three RyR isoforms at [Ca 2ϩ ] Ͼ 1 M, whereas at [Ca 2ϩ ] Ͻ 1 M RyR1 and RyR3 are activated, but RyR2 is inhibited by CaM (6,7). 35 S-CaM binding to sarcoplasmic reticulum vesicles (8,9) and purified RyR1 and RyR2 (10) showed that the two receptor isoforms bind one molecule of CaM per RyR subunit in the absence and presence of Ca 2ϩ . CaM protection of trypsin digestion of RyR1 (11) and site-directed mutagenesis of RyR1 (12) and RyR2 (13) demonstrated that the two RyRs have a single CaM regulatory binding domain (CaMBD) (aa 3614 -3643 in RyR1) for the Ca 2ϩ -free and Ca 2ϩ -bound (Ca 2ϩ -CaM) forms of CaM.…”
mentioning
confidence: 99%